Pólo industrial exportador: desafios para o novo papel da zona franca de Manaus - Bispo, Jorge de Souza (2003)
This job intends to identify and study the main technical, administrative and bureaucratic hindrances that challenge the Manaus Free Zone consolidation as an Industrial Exportation Pole. Such study has been based on technical bibliography, federal legislation and field research. The hypothesis states that administrative, technical and bureaucratic hindrances exist and that they are really challenging, making difficult the consolidation of the industrial park located in the Free Zone, in Manaus. Thus, this hypothesis allows a tactful study on the challenges, which are to be faced by the current and potential exporters.